The Impact of Loneliness and Depression on Cardiovascular Disease Management in Older Adults - Rogowska, Wiktoria; Sado, Aleksandra; Kozyra, Klaudia; Kozieł-Kwit, Sylwia; Lisik, Bartłomiej; Sawczuk, Kacper; Simlat, Aleksandra; Szada-Borzyszkowski, Krzysztof; Wręczycki, Mariusz; Skowierzak, Filip (Journal of Education, Health and Sport, 2026)
Background. Loneliness and depression are increasingly recognized as key determinants of cardiovascular health in older adults, affecting biological stress systems, inflammation, behaviors, and adherence. Aim. The review summarizes studies from 2018-2025 on the association between loneliness, depression, and cardiovascular diseases in older adults, focusing on hypertension, behavioural factors, and the role of primary care in integrated psychosocial and cardiovascular management. Materials and Methods. A literature search was conducted using PubMed, Springer Nature Link, Via Medica, ScienceDirect and MDPI. Cohort studies, meta-analyses, and interventional trials on psychosocial determinants of cardiovascular disease in older adults. Results. Loneliness and depression activate biological stress systems (HPA axis dysregulation, sympathetic overactivity, elevated IL-6/CRP), leading to endothelial dysfunction and accelerated atherosclerosis. Behavioral factors such as physical inactivity, poor diet, smoking, and reduced adherence further increase cardiovascular risk. Social isolation and low family support worsen disease control. Depression reduces medication adherence by 40–45% and is associated with poorer blood pressure control, higher cardiac events and mortality. Primary care is crucial for early detection, yet depression remains underdiagnosed in older adults. Conclusion. Loneliness and depression substantially impair cardiovascular outcomes in older adults via biological, behavioral, and psychosocial pathways. Integrating psychosocial assessment, depression screening, and supportive interventions into routine cardiovascular care can improve adherence, strengthen social support, and enhance long-term prognosis.